The Shaping of Grand Strategy : Policy, Diplomacy, and War - Murray, Williamson; Sinnreich, Richard Hart; Lacey, James (Cambridge : Cambridge University Press, 2011)
Within a variety of historical contexts, The Shaping of Grand Strategy addresses the most important tasks states have confronted: namely, how to protect their citizens against the short-range as well as long-range dangers their polities confront in the present and may confront in the future. To be successful, grand strategy demands that governments and leaders chart a course that involves more than simply reacting to immediate events. Above all, it demands they adapt to sudden and major changes in the international environment, which more often than not involves the outbreak of great conflicts but at times demands recognition of major economic, political, or diplomatic changes. This collection of essays explores the successes as well as failures of great states attempting to create grand strategies that work and aims at achieving an understanding of some of the extraordinary difficulties involved in casting, evolving and adapting grand strategy to the realities of the world.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).